Development of dietary KAP（knowledge， attitude and practice）questionnaires for patients with type 2 diabetes mellitus and their family members and assessment of reliability and validity - LIU Shuhong, YANG Dan, HU Xiling, GUO Xiaodi, ZHANG Yao (Xin yixue)
Objective To develop two versions of dietary KAP（knowledge， attitude and practice）questionnaires among patients with type 2 diabetes mellitus （T2DM） and their family members， and to assess the reliability and validity， aiming to provide reference for medical staff regarding dietary education and management. Methods Based on KAP theory， the initial edition was compiled by literature reviews， semi-structured interviews， and two rounds of expert consultation. A total of 236 patients with T2DM admitted to Department of Endocrinology of the Third Affiliated Hospital of Sun Yat-sen University from June to December 2023 and their family members were selected by convenience sampling method， and the questionnaire was analyzed and tested for reliability and validity. Results Two versions of questionnaires on dietary KAP among patients with T2DM and their family members were developed. The questionnaire included three dimensions： knowledge， attitude and practice， with a total of 39 items. The item analysis and the validity of the questionnaire content reached the standard. Total Cronbach’s alpha for the questionnaire was 0.926 （patient version） and 0.946 （family version）. The Cronbach’s alpha for the three dimensions of knowledge， attitude and behavior were 0.944， 0.884， 0.825 （patient version） and 0.941， 0.928， 0.932 （family version）. Three common factors were extracted by exploratory factor analysis， and the cumulative variance contribution rates were 44.5% （patient version） and 53.4% （family member version）. The confirmatory factor analysis showed that the Chi-square degree of freedom ratio was calculated as 2.36 （patient version） and 2.58 （family member version）， the comparative fit index was 0.84 （patient version） and 0.81 （family member version）， the Tucker Lewis index was 0.83 （patient version） and 0.80 （family member version）， and the approximate root mean square error was 0.07 （patient version） and 0.08 （family member version）， respectively. Content validity analysis showed that the item-level content validity index was 0.938-1.000， and the average scale-level content validity index was 0.977 （patient version） and 0.968 （family member version）. Conclusion The dietary KAP questionnaires among T2DM patients and their family members developed in this study yield high reliability and validity， which could be an effective dietary assessment tool for patients with diabetes mellitus.